Erythropoietin therapy improves endothelial function in patients with non-dialysis chronic kidney disease and anemia (EARNEST-CKD): A clinical study. Issue 42 (22nd October 2021) - Lim, Jina; Yu, Chung Jo; Yu, Hoon; Ha, Sang Jin
Abstract: Background: This study investigated whether administering erythropoiesis-stimulating agents (ESAs) improves endothelial function in patients with non-dialysis chronic kidney disease (CKD) and anemia. Methods: This single-center, prospective, single-arm comparison study enrolled patients with non-dialysis CKD (stages 4-5) and hemoglobin levels <10 g/dL. ESA administration followed the Kidney Disease: Improving Global Outcomes guideline. The primary endpoint was the change in flow-mediated dilatation after ESA administration in individual patients. The secondary endpoints were changes in 6-minute walk test results, blood pressure, New York Heart Association class, and echocardiographic parameters. The echocardiographic parameters examined included chamber quantification, Doppler parameters, and systolic and diastolic function parameters. Results: Initially, 13 patients were screened, but 2 discontinued due to either heart failure or voluntary withdrawal. The mean flow-mediated dilatation values significantly increased by 10.59% (from 1.36% ± 1.91% to 11.95% ± 8.11%, P = .001). Echocardiographic findings showed that the left ventricular mass index decreased by 11.9 g/m 2 (from 105.8 ± 16.3 to 93.9 ± 19.5 g/m 2, P = .006 ), and the left atrial volume index decreased by 10.8 mL/m 2 (from 50.1 ± 11.3 to 39.3 ± 11.3 mL/m 2, P = .004) after 12 weeks of ESA administration. There were no significant differences between pre- and post-ESA treatment 6-minute walk test results. No significant side effects were observed during the study period. Conclusions: This is the first clinical study to demonstrate that an ESA improves endothelial dysfunction, left ventricular hypertrophy, and left atrial volume in patients with non-dialysis CKD. Thus, ESAs may be considered as adjunctive therapy for reducing cardiovascular risk in these patients.